A METHOD OF IMPULSE NOISE DETECTION BY USING LAPLACIANGAUSSIAN FILTER ADAPTED WITH GENETIC ALGORITHM - Al_anizy, Maisaa (Iraqi Journal of Science, 2024)
In this paper, impulse noise detector found in an image by using Laplacian-Gaussianfilter is proposed. The LG filter used for smoothing the noise in image. The flat parts ofcontour, detected by a set of different threshold for noise detected to perform the task ofremoving impulse noise. Finally, based on the genetic algorithm, the genetic learning theprocess adjusts the parameters of image base. Based on the criteria of Peak Signal toNoise Ratio(PSNR), Mean Square Error(MSE) and Mean Absolute Error(MAE) toachieves a better performance that proposed method performs significantly better thantraditional methods